MAVEN/IUVS Stellar Occultation Measurements of Mars Atmospheric Structure and Composition. Issue 6 (14th June 2018) - Gröller, H.; Montmessin, F.; Yelle, R. V.; Lefèvre, F.; Forget, F.; Schneider, N. M.; Koskinen, T. T.; Deighan, J.; Jain, S. K.
Abstract: The Imaging UltraViolet Spectrograph (IUVS) instrument of the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission has acquired data on Mars for more than one Martian year. During this time, beginning with March 2015, hundreds of stellar occultations have been observed, in 12 dedicated occultation campaigns, executed on average every 2 to 3 months. The occultations cover the latitudes from 80°S to 75°N and the full range longitude and local times with relatively sparse sampling. From these measurements we retrieve CO2, O2, and O3 number densities as well as temperature profiles in the altitude range from 20 to 160 km, covering 8 orders of magnitude in pressure from ∼2 × 10 1 to ∼4 × 10 −7 Pa. These data constrain the composition and thermal structure of the atmosphere. The O2 mixing ratios retrieved during this study show a high variability from 1.5 × 10 −3 to 6 × 10 −3 ; however, the mean value seems to be constant with solar longitude. We detect ozone between 20 and 60 km. In many profiles there is a well‐defined peak between 30 and 40 km with a maximum density of 1–2 ×10 9 cm −3 . Examination of the vertical temperature profiles reveals substantial disagreement with models, with observed temperatures both warmer and colder than predicted. Examination of the altitude profiles of density perturbations and their variation with longitude shows structured atmospheric perturbations at altitudes above 100 km that are likely nonmigrating tides. These perturbations are dominated by zonal wave numbers 2 and 3 with amplitudes greater than 45%. Key Points: The execution of MAVEN/IUVS stellar occultation campaigns and the retrieval process to infer physical quantities are described in detail Distribution of molecular oxygen and ozone is measured Highly structured atmospheric perturbations are interpreted as atmospheric tides